2020
DOI: 10.1111/jbi.13915
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing historical shifts in suitable habitat of Sceloporus lineages using phylogenetic niche modelling

Abstract: Aim: We tested whether we could detect geographical shifts in modelled-suitable habitat. We aim to enhance phylogenetic niche models of past suitable habitats for Sceloporus lineages by integrating modern and fossil occurrences with ecological and phylogenetic comparative modelling methods. Specifically, we hypothesized that our integrated approach is sensitive enough to detect geographical shifts in suitable habitat between lineages and through evolutionary time. Location: North America. Taxon: Sceloporus liz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 78 publications
(110 reference statements)
0
21
0
Order By: Relevance
“…The undulatus clade seems to exemplify Rapoport's rule (Stevens, 1989) as the group is found at higher latitudes and species have exceptionally large ranges with only two widespread undulatus species occurring in the Southeast United States and two widespread undulates species occurring in the Midwest United States. The group seems to have migrated over large distances in a relatively short period of time (Rivera et al., 2020) with few speciation events occurring. Additionally, the group shows little phenotypic diversification (Leaché, 2009) with most species being medium in body size while only two species, S. woodi and S. virgatus , were small.…”
Section: Discussionmentioning
confidence: 99%
“…The undulatus clade seems to exemplify Rapoport's rule (Stevens, 1989) as the group is found at higher latitudes and species have exceptionally large ranges with only two widespread undulatus species occurring in the Southeast United States and two widespread undulates species occurring in the Midwest United States. The group seems to have migrated over large distances in a relatively short period of time (Rivera et al., 2020) with few speciation events occurring. Additionally, the group shows little phenotypic diversification (Leaché, 2009) with most species being medium in body size while only two species, S. woodi and S. virgatus , were small.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is clear that more work is needed to better understand the evolution of physiological tolerances and how they relate to the climate space in which species occur. Rivera et al (2020) honed this framework to investigate lineage-specific differences among congeners. They showed that large shifts in the climate system drove expansion and contraction of suitable habitat and that geologic events, such as orogeny, relate to diversification events.…”
Section: Paleophylogeographic Species Distribution Models (Ppgms)mentioning
confidence: 99%
“…This allowed for more nuanced phylogenetic reconstruction of climate envelopes and more nuanced paleoclimate estimations between time periods where there are available global atmosphere and ocean circulation models reconstructing paleoclimate across geographic space. Second, PPGMs incorporated a method to include paleoclimate information associated with fossil localities into phylogenetic climate envelope reconstructions (Lawing et al 2016; Rivera et al 2020). If the paleoclimate information shows that a fossil occurred in a climate that is outside the distribution of current climates for a group under evaluation, then that information can improve our understanding of the evolution of climate envelopes and the paleobiogeographic reconstruction of species.…”
Section: Paleophylogeographic Species Distribution Models (Ppgms)mentioning
confidence: 99%
See 2 more Smart Citations